2018
DOI: 10.1002/bse.2176
|View full text |Cite
|
Sign up to set email alerts
|

Limited progress in sustainable development: Factors influencing the environmental management and reporting of South African JSE‐listed companies

Abstract: Although public, governmental, international and stakeholder pressure have led to corporations conforming to better sustainability performance, there has been an insignificant reduction in environmental degradation levels, and progress in sustainable development is limited. This study examines which factors influencing environmental management and reporting in South Africa could potentially contribute to this limited progress. The study was based on a series of interviews with sustainability managers of JSE‐li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…To address these challenges, an increasing number of firms have started to reorganize their BoDs through the introduction of CSR committees (WBCSD, 2019). The presence of a CSR committee signals an orientation to sustainability themes due to its voluntariness (Kitsikopoulos et al, 2018). Furthermore, prior studies have reported that the phenomenon affects non‐financial reporting quality.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…To address these challenges, an increasing number of firms have started to reorganize their BoDs through the introduction of CSR committees (WBCSD, 2019). The presence of a CSR committee signals an orientation to sustainability themes due to its voluntariness (Kitsikopoulos et al, 2018). Furthermore, prior studies have reported that the phenomenon affects non‐financial reporting quality.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Despite extensive discourse on materiality by researchers and standard setters, the concept may still be regarded as inherently nondistinctive due to the lack of a clear dividing line between material and nonmaterial matters (Bernstein, ; Kitsikopoulos, Schwaibold, & Taylor, ; Lo, ; Whitehead, ). As such, materiality inevitably provides companies with administrative discretion for expectation management and favorable self‐display (Edgley, ; Stubbs & Higgins, ).…”
Section: Introductionmentioning
confidence: 99%
“…Capturing how companies' low-carbon transition plan is supported by debt financing activities and how capital is raised for existing and new projects with climate benefits nonfinancial disclosure, in turn, is a form of corporate responsibility to society and a way of fulfilling the information needs of investors, employees, customers, ecologists, and other parties. Continuous environmental degradation has triggered increased stakeholder pressure on companies to change their behavior and focus more on their environmental impacts (Kitsikopoulos et al 2018;Helfaya and Moussa 2017;Isaacs et al 2015;Johnson et al 2013;Hovardas and Poirazidis 2007). Prior research has analyzed stakeholder pressures and corporate responses (Sprengel and Busch 2010) with regard to environmental strategies (Seroka-Stolka and Fijorek 2020).…”
Section: Physical Risksmentioning
confidence: 99%